Planning to improve global health: the next decade of tuberculosis control - Dermot Maher; Chris Dye; Katherine Floyd; Andrea Pantoja; Knut Lonnroth; Alasdair Reid; Eva Nathanson; Thad Pennas; Uli Fruth; Jane Cunningham; Heather Ignatius; Mario C Raviglione; et al. (The World Health Organization, 2007)
The Global Plan to Stop TB 2006-2015 is a road map for policy-makers and managers of national programmes. It sets out the key actions needed to achieve the targets of the Millennium Development Goals relating to tuberculosis (TB): to halve the prevalence and deaths by 2015 relative to 1990 levels and to save 14 million lives. Developed by a broad coalition of partners, the plan presents a model approach combining interventions that can feasibly be supplied on the ground. The main areas of activity set out in the plan are: scaling up interventions to control tuberculosis; promoting the research and development of improved diagnostics, drugs and vaccines; and engaging in related activities for advocacy, communications and social mobilization. Scenarios for the planning process were developed; these looked at issues both globally and in seven epidemiological regions. The scenarios made ambitious but realistic assumptions about the pace of scale-up and implementation coverage of the activities. A mathematical model was used to estimate the impact of scaling up current interventions based on data from studies of tuberculosis biology and from experience with tuberculosis control in diverse settings. The estimated costs of the activities set out in the Global Plan were based on implementing interventions and researching and developing drugs, diagnostics and vaccines; these costs were US$ 56 billion over 10 years. When translated into cost per disability adjusted life year averted, these costs compare favourably with those of other public health interventions. This approach to planning for global tuberculosis control is a valuable example of developing plans to improve global health that has relevance for other health issues.